Singgah / Anis Farahin Faisal - Faisal, Anis Farahin (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2024)
This interpretation centre is a heritage centre which focuses on the Santubong Malay history of Sarawak and the forgotten individiuals who were involved in the success of the lands. Santubong regarded as one of the oldest Malay state in the world and despite that, it is know to many and has only been acknowledge by a few specialist. The idea of “TRAIL OF REMNANTS” is used in the designing process to signifiy the abundance of historical value of the land that has been disregarded and forgotten due to the lack of exposure. The centre aims to rekindle these histories.